Recontextualization of Islamic-Malay Ethics through Modern Zapin: A Didactic Analysis of Lesti Kejora's Song in Character Education - Fathin, Syarifah; Permadini, Susan (Universitas Islam Negeri Raden Fatah Palembang, 2025)
The erosion of cultural identity among Generation Z necessitates an innovative approach to character education through the recontextualization of local wisdom. This study aims to analyze the integration of moral and cultural values within the song